2014
DOI: 10.1002/chem.201404292
|View full text |Cite
|
Sign up to set email alerts
|

BODIPY‐Based Oligo(ethylene glycol) Dendrons as Fluorescence Thermometers: When Thermoresponsiveness Meets Intramolecular Electron/Charge Transfer

Abstract: The temperature-dependent photophysical properties of a series of 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) derivatives with different oligo(ethylene glycol) (OEG) dendrons were investigated. Weak fluorescence emission was observed for these BODIPY derivatives in dilute solution with low viscosity. BDP-G0 and BDP-G1-TEG exhibit a high quantum yield in viscous glycerol solutions, contrary to the moderate and little fluorescence enhancement for BDP-G1 and BDP-G2 under the same conditions. The photoindu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…The emission band of BBDP was located in the NIR range on account of the extensive conjugated pyrene–BODIPY architecture. Besides, BBDP showed small Stokes shifts in various solvents (less than Δ λ =30 nm), which indicated that there were weak intramolecular donor–acceptor interactions in the ground state . More information about the photophysical data of BBDP are summarized in Table S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The emission band of BBDP was located in the NIR range on account of the extensive conjugated pyrene–BODIPY architecture. Besides, BBDP showed small Stokes shifts in various solvents (less than Δ λ =30 nm), which indicated that there were weak intramolecular donor–acceptor interactions in the ground state . More information about the photophysical data of BBDP are summarized in Table S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Formyl-modified OEG dendrons 1 followed ac lassic synthetic pathway to BODIPY derivatives to afford target molecule 2. [45] Then, compound 2 underwent aK noevenagel reactionw ith 1-pyrenecarboxaldehydet og enerate the final BBDP product. [26] PBI and MV were obtained according to the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the luminescent POPs with tunable surface morphologies have rarely been referred. We have been interested in fluorescent amphiphilic 4,4‐difluoro‐4‐bora‐3a,4a‐diaza‐s‐indacene (BDP) derivatives since 2014 . Very recently, a novel about dimeric BDP molecules based POPs could be realized by using FeCl 3 at room temperature was reported .…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] For example, the styryl-substituted BODIPY could effectively induce a red shift of the absorption and emission maxima. 45 The water-soluble BODIPY chemosensors have also received much attention, which could be achieved by introducing some hydrophilic moieties such as oligo-(ethyleneglycol) chains, [46][47][48][49][50] sulfonates, 51-53 phosphonates 54 and zwitterionic sulfobetaines. 32 However, for most of the small molecular Hg 2+ chemosensors, their water solubility is very limited, since these chemosensors are hydrophobic and have big rigid conjugated planes inducing aggregation between them.…”
Section: Introductionmentioning
confidence: 99%